2001
DOI: 10.1128/jvi.75.16.7462-7469.2001
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genotypic Changes in Human Immunodeficiency Virus Protease That Correlate with Reduced Susceptibility to the Protease Inhibitor Lopinavir among Viral Isolates from Protease Inhibitor-Experienced Patients

Abstract: The association of genotypic changes in human immunodeficiency virus (HIV) protease with reduced in vitro susceptibility to the new protease inhibitor lopinavir (previously ABT-378) was explored using a panel of viral isolates from subjects failing therapy with other protease inhibitors. Two statistical tests showed that specific mutations at 11 amino acid positions in protease (L10F/I/R/V, K20M/R, L24I, M46I/L, F53L, I54L/T/V, L63P, A71I/L/T/V, V82A/F/T, I84V, and L90M) were associated with reduced susceptibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
146
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(156 citation statements)
references
References 22 publications
8
146
2
Order By: Relevance
“…The V82A occurs predominantly in HIV-1 isolates from patients receiving treatment with IDV or RTV (Condra et al 1996, Molla et al 1996. By themselves, mutations at position 82 confer reduced susceptibility in vitro to IDV, RTV, and LPV but not to NFV, SQV, or APV (Kempf et al 2001). However, when present with other PI mutations, V82A contributes to clinical resistance to each of the PIs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The V82A occurs predominantly in HIV-1 isolates from patients receiving treatment with IDV or RTV (Condra et al 1996, Molla et al 1996. By themselves, mutations at position 82 confer reduced susceptibility in vitro to IDV, RTV, and LPV but not to NFV, SQV, or APV (Kempf et al 2001). However, when present with other PI mutations, V82A contributes to clinical resistance to each of the PIs.…”
Section: Discussionmentioning
confidence: 99%
“…et al 2000a) and has not been shown to confer crossresistance to other PIs, except possibly LPV (Kempf et al 2001). Both children were receiving NFV or RTV and presented possible resistance to LPV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although 16 antiretroviral drugs have been approved for the treatment of HIV-1, cross-resistance within each of the three antiretroviral drug classes-nucleoside reverse transcriptase (RT) inhibitors, nonnucleoside RT inhibitors, and protease inhibitors-often leads to the development of multidrug resistance. HIV-1-specific protease inhibitors pose a high genetic barrier to drug resistance because multiple protease mutations are usually required for the development of resistance to these inhibitors (4,13,19). Nonetheless, resistance to multiple protease inhibitors occurs commonly, attesting to the conformational flexibility of the HIV-1 protease enzyme (5,10,13,26).…”
mentioning
confidence: 99%
“…When suppression of HIV-1 replication by PI-containing therapy is incomplete, variants with reduced sensitivity to the PI can emerge by accumulating nonsynonymous mutations in the PR gene (4,14,17,20), causing a serious reduction in the clinical efficacy of HAART (1,5,10). PI resistance-associated mutations often affect the substrate specificity of PR (8) and can impair enzyme function, resulting in reduction of the replicative capacity of the variants (2,7,(16)(17)(18)28).…”
mentioning
confidence: 99%